Centros de Educação e Alimentação do Pré-Escolar: solução alternativa de atendimento integral ao pré-escolar Preschool Education and Feeding Centre - CEAPE: an alternative solution to the problem of all-round preschool assistance - Yaro Ribeiro Gandra (Universidade de São Paulo, 1981)
São resumidas as bases filosóficas e operacionais do programa de Educação e Alimentação do Pré-Escolar (CEAPE), que inclui: a educação e a participação ativa da mãe do pré-escolar; a promoção do treinamento de multiplicadores locais da ação programada; a avaliação da eficiência e da eficácia do programa por meio de indicadores pré-testados. São evidenciadas as vantagens do programa, a saber: é econômico porque usa a infra-estrutura local, utiliza a cooperação das mães dos pré-escolares e a supervisão do pessoal ligado ao ensino; é eficiente porque oferece e amplia o atendimento aos pré-escolares; é eficaz porque propicia realmente melhor desenvolvimento integral da criança; é preventivo porque melhora as condições físicas e de aprendizado do pré-escolar; é comunitário porque por meio da "mãe" envolve a comunidade onde a criança vive. The basic philosophy of the CEAPE here summarized is the expansion of supplementary feeding and global assistance to preschoolers to prepare them physically, mentally and socially for normal activities and for the first phases of their schooling. The program includes the active participation and education of mothers of preschool children and provides training for "multiplies" to participate in the CEAPE. Many programs using the CEAPE philosophy are being created all over the country. CEAPE is economical because it makes use of local facilities and structures of unused school space, mothers' cooperation and collaboration of teaching personnel. It is efficient because it increase and controls assistance to preschool children and involves the community through the mother's ascendency. Also it is efficacious as it contributes to the physical, social, educational and psychomotor development of the child. It also contributes to the education of the preschooler mothers. It is preventive because it improves the health of the children as well as preparing them for school, decreasing failure and drop-out rates of the first and second years of primary school.